Advances in Photodiodes - Franco Dalla Betta, Gian (IntechOpen, 2011)
Photodiodes, the simplest but most versatile optoelectronic devices, are currently used in a variety of applications, including vision systems, optical interconnects, optical storage systems, photometry, particle physics, medical imaging, etc. Advances in Photodiodes addresses the state-of-the-art, latest developments and new trends in the field, covering theoretical aspects, design and simulation issues, processing techniques, experimental results, and applications. Written by internationally renowned experts, with contributions from universities, research institutes and industries, the book is a valuable reference tool for students, scientists, engineers, and researchers.